Global Habitus: Collectivist and Individualist Values in Cultural Capital among Chinese Malaysian Youth - Rachel Chan Suet Kay; Juli Edo; Rosila Bee Hussain (Kajian Malaysia, 2016)
This paper highlights how Chinese-educated Chinese Malaysian undergraduate youth display a preference for not only collectivist but also individualist values, as indicated by the cultural capital based on preference in books. The study is based on the theoretical framework of cultural capital as introduced by sociologist Pierre Bourdieu, and the choice of book preference as indicator follows a large scale study of modern China by Wang, Davis and Yanjie (2006). It is found that contrary to literature which suggests that the Chinese diaspora are more prone to collectivism, respondents of this small-scale study show openness to both collectivist and individualistic values. This indicates a cultural homogenisation effect on the cultural capital possession of respondents. As the study only includes a convenience sample of Chinese Malaysian undergraduates pursuing their undergraduate study through a Chinese-language medium, the findings are not meant to generalise the entire population.